Photocatalytic degradation of industrial dye wastewater using zinc oxide polyvinylpyrrolidone nanoparticles - Abu Bakar Sidik, Dilaelyana; Hairom, Nur Hanis Hayati; Zainuri, Nur Zarifah; Desa, Amira Liyana; Misdan, Nurasyikin; Yusof, Norhaniza; Chin, Boon Ong; Mohammad, Abdul Wahab; Mohd Aripen, Nur Shahirah (The Malaysian Analytical Sciences Society, 2018)
Due to the lack of studies regarding the potential of polyvinylpyrrolidone (PVP) as capping agent in precipitation of zinc oxide (ZnO) nanoparticles, this research focused on the performance of ZnO nanoparticles with presence of PVP loading on photocatalytic degradation treatment for industrial dye wastewater. Three different samples of ZnO-PVP were successfully synthesized via precipitation method. The degradation rate of dye approached 90.61% under pH7 in the presence of ZnO-PVP (0.025g/L of PVP). The chemical bonds in ZnO-PVP was analysed using Fourier Transform Infrared Spectroscopy (FTIR).